Threshold response of C15 to the Dpp gradient in Drosophila is established by the cumulative effect of Smad and Zen activators and negative cues. - Lin, M.C.; Park, J.; Kirov, N.; Rushlow, C. (Development, 2006)
Morphogen gradients determine a range of cell fates by specifying multiple transcriptional threshold responses. In the dorsal ectoderm of the Drosophila embryo, a BMP gradient is translated into an activated Smad transcription factor gradient, which elicits at least three threshold responses - high, intermediate and low. However, the mechanism underlying differential response to Dpp is poorly understood, due in part to the insufficient number of well-studied target genes. We analyzed the regulation of the C15 gene, which can be activated in cells containing intermediate levels of Dpp. We show that C15 expression requires both dpp and zen, thus forming a genetic feed-forward loop. The C15 regulatory element contains clusters of Smad- and Zen-binding sites in close proximity. Mutational analysis shows that the number of intact Smad- and Zen-binding sites is essential for the C15 transcriptional response, and that the spatial limits of C15 expression are established through a repression mechanism in the dorsolateral cells of the embryo. Thus, the combinatorial action of Smad and Zen activators bound to a number of adjacent sites, and competing negative cues allows for proper gene response to lower than peak levels of the Dpp morphogen.